Studi Pembelajaran Kooperatif Tipe Student Teams Achievement Division dalam Pembelajaran Instalasi Penerangan Listrik - Rahayu, Wiwik; Mulya, Rudi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
Based on the author's observations, the learning method at SMKN 5, a conventional learning system, still dominates Padang.Conventional learning systems and student learning outcomes have not been satisfactory, including in IPL subjects. Satisfactory, including in IPL subjects. This research aims to determine whether student learning outcomes using cooperative learning type STAD is better than conventional learning. This research hypothesizes that IPL learning outcomes of students using STAD-type cooperative learning are better than those of conventional learning. is better than IPL learning outcomes of students who use conventional learning in class XI of the Electrical The learning outcomes of students using STAD-type cooperative learning are better than those using conventional learning in class XI of the Electrical Department of SMKN 5 Padang. This research is experimental with the design model Randomized Control group-only design model. The sample of this study was students from class XI L2, which was the experimental class, and XIL3, the control class. Experimental class and XIL3 as a control class. The research instrument was a test. Data In this study, the data were processed using SPSS version 23.0 software. From the results of the study obtained the average learning outcomes of experimental class students are greater than those of the control class and from the t-test results obtained t-test results obtained a t value that was more significant than the t table; this means that STAD-type cooperative learning is better than conventional learning. STAD-type cooperative learning is better than conventional learning. In this research, This study also revealed that the learning completeness of experimental class students was also more significant than that of the control class.